2017
DOI: 10.5455/njppp.2017.7.0411310042017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antianxiety activity of ethanolic extract of leaves of Ocimum sanctum (tulsi) in albino mice

Abstract: Background: Anxiety is a normal emotional behavior, however, becomes pathological precipitating cardiovascular and psychiatric disorders when it is severe. Many allopathic drugs are available to treat anxiety disorders, among which benzodiazepines are most commonly used which possess various systemic side effects. Aims and Objectives: In our study, we have attempted to evaluate new compound Ocimum sanctum (OS) in the hope of identifying the anxiolytics with fewer side effects as many plant products have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The light-dark box test is based on the inherent nature of mice to avoid brightly illuminated places. Manu et al reported that with the use of anxiolytic the time spent in the light compartment found to be increased [22]. In the present study META200 and 400mg/kg showed significant dose-dependent increase in entries and stay in the open arms in EPM and entries and stay in the light compartment in LDB as compared to control.…”
Section: Discussionsupporting
confidence: 54%
“…The light-dark box test is based on the inherent nature of mice to avoid brightly illuminated places. Manu et al reported that with the use of anxiolytic the time spent in the light compartment found to be increased [22]. In the present study META200 and 400mg/kg showed significant dose-dependent increase in entries and stay in the open arms in EPM and entries and stay in the light compartment in LDB as compared to control.…”
Section: Discussionsupporting
confidence: 54%
“…This apparatus, elevated from the floor, comprises two open arms and two closed arms, which have been extended from a central platform. In general, the mice were selected and classified into groups, as mentioned as follows: Group I (control): mice ( n = 6) received normal saline orally (NaCl, 0.9% 10 ml/kg) Group II (standard): mice ( n = 6) received an oral injection of 1 mg/kg [ 18 ] Group III (test): mice ( n = 6) received 500 mg/kg of aqueous Sp extract orally [ 19 ] Group IV (test): mice ( n = 6) received 500 mg/kg of Sp ethyl acetate extract orally [ 20 ] …”
Section: Methodsmentioning
confidence: 99%
“…Group I (control): mice (n � 6) received normal saline orally (NaCl, 0.9% 10 ml/kg) Group II (standard): mice (n � 6) received an oral injection of 1 mg/kg [18] Group III (test): mice (n � 6) received 500 mg/kg of aqueous Sp extract orally [19] Group IV (test): mice (n � 6) received 500 mg/kg of Sp ethyl acetate extract orally [20] Te mice were placed separately in the maze's centre, head facing towards the open arm. Te number of entries in the open and closed arms and the total time spent in open and closed arms, respectively, were recorded for 5 min (entry into an arm is described as the animal placing all four paws onto the arm).…”
Section: Behavioral Paradigms 251 Anxiety Modelmentioning
confidence: 99%